Monodispersed Hierarchical γ-AlOOH/Fe(OH)3 Micro/Nanoflowers for Efficient Oxygen Evolution Reaction - Huo, Wang; Li, Li; Zhang, Yongxing; Li, Jia; Xu, Qianqian; Zhang, Baojie; Zhang, Lei; Li, Xuanhua (Frontiers in Materials, 2019)
Exploring efficient and inexpensive nanostructured catalysts for the oxygen evolution reaction (OER) is critical for economical electrochemical water splitting. Here, monodispersed γ-AlOOH/Fe(OH)3 with hierarchical structures have been synthesized by a facile hydrothermal method and an electrostatic attraction treatment. The low overpotential of only 289 mV at a current density of 10 mA cm-2 for γ-AlOOH/Fe(OH)3 with a low Tafel slope of 80.2 mV dec-1, which is greatly decreased than that of γ-AlOOH (347 mV and 88.4 mV dec-1 ). The monodispersed γ-AlOOH/Fe(OH)3 with hierarchical structures and abundance of surface hydroxyls have high specific surface areas and large pore volumes, which can provide more active sites to help the transfer of the electrons to improve the electrocatalytic performance for OER.